Overview of GLOBUS-M2 spherical tokamak results at the enhanced values of magnetic field and plasma current. (7th February 2022) - Petrov, Yu.V.; Gusev, V.K.; Sakharov, N.V.; Minaev, V.B.; Varfolomeev, V.I.; Dyachenko, V.V.; Balachenkov, I.M.; Bakharev, N.N.; Bondarchuk, E.N.; Bulanin, V.V.; Chernyshev, F.V.; Iliasova, M.V.; et al.
Abstract: The paper provides an overview of the results obtained on the spherical tokamak Globus-M2 in 2019–2020. The experiments were performed with the toroidal magnetic field up to 0.8 T and plasma current up to 0.4 MA (80% of the design values). The temperature of electrons 1 keV and ions 800 eV at the plasma density of 10 20 m −3 were recorded at neutral beam injection (850 kW, 28.5 keV). Heat conductivity analysis was made by means of the codes ASTRA 7.0, NCLASS, SPIDER, NUBEAM, 3D fast ion tracking algorithm on the basis of the experimental data. A scaling for spherical tokamaks, which demonstrates strong τ E dependence on magnetic field and moderate dependence on plasma current, has been confirmed for the magnetic field up to 0.8 T. For Globus-M/M2 it is τ E GLB ∼ I p 0.43 ± 0.22 B T 1.19 ± 0.1 . The dependence of the normalized energy confinement time ( B T τ E ) on collisionality ( ν *) in a wide range 0.02 < ν * < 0.2 was determined as B T τ E ∼ ν * − 0.74 . A non-inductively driven current was recorded during the launch of the electromagnetic waves of the lower hybrid frequency range (2.45 GHz) with the help of a toroidally oriented grill. The fraction of noninductively driven current has exceeded 70% in the discharge with a total current of 0.2 MA. The achieved values of efficiency η = (0.15–0.4) × 10 19 A m −2 W −1 are comparable with the results obtained on conventional tokamaks. This paper presents the results of experiments on the study of Alfvén modes. The resulting scaling for the loss of fast ions caused by toroidal Alfvén eigenmodes demonstrates their decrease with increasing magnetic field and plasma current. Observation of Alfvén cascades made it possible to apply the method of MHD spectroscopy to determine the evolution of q min in a discharge. Also presented are the results of SOL investigation. Attention is also paid to the development of diagnostics.